Monovalent alkali metal ion separation composite membrane as well as preparation method and application thereof
By using a composite membrane of two-dimensional materials and heteropolyacids in membrane separation technology, the exchange barrier of monovalent alkali metal ions is optimized, and the problem of removing monovalent cationic impurities in salt lake brine is solved, and the efficient extraction and high-quality lithium ions are achieved The separation ratio improves the utilization efficiency of lithium resources.
Patent Information
- Application Number
- CN202411575573.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-06
AI Technical Summary
Existing membrane separation technology is difficult to efficiently remove monovalent cationic impurities in salt lake brine, such as sodium ions and potassium ions, which affects the extraction efficiency of lithium ions.
Using a composite film containing two-dimensional materials and heteropolyacids, the exchange barrier between heteropolyacids and monovalent alkali metal ions is adjusted, and the transfer rate of lithium ions and other monovalent alkali metal ions are optimized to achieve high separation ratio. lithium ion separation.
It realizes rapid transmission and high separation ratio of lithium ions, improves the extraction efficiency of lithium ions, reduces the cost and energy consumption of the separation process, and is suitable for the efficient utilization of lithium resources in salt lakes.
Smart Images

Figure CN119186279A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ion separation membranes, and more specifically, relates to a monovalent alkali metal ion separation composite membrane and a preparation method and application thereof. Background Art
[0002] Lithium mining has become critical, driven by the rapid growth in demand for lithium from sustainable energy. Extracting lithium from aquatic sources (such as salt lakes) requires efficient and environmentally friendly separation technologies. Membrane separation technology has the advantages of low energy consumption, environmental friendliness, and no phase change in lithium extraction, which makes it an effective method for efficiently separating lithium ions from salt lake brines. Membrane separation technology has basically solved the key challenge of removing calcium and magnesium ions from salt lake brines. However, due to the slight differences in radius and dehydration energy between monovalent cations present in salt lake brines, the removal of other monovalent cation impurities (such as sodium ions and potassium ions) is still a major problem that membrane separation technology has not yet overcome. Through further research and development, separation membranes based on new two-dimensional materials are expected to solve the bottleneck of existing membrane separation technology and provide important support for the efficient utilization of lithium resources and the development of new energy industries.
[0003] As a biomimetic target for ion separation membranes, potassium ion channels (KcsA) show extremely high monovalent cation selectivity due to their subnanometer channels and precise coordination of ions with their carbonyl groups. Inspired by this, various oxygen-containing organic ligand designs, such as crown ethers or sulfonates, have emerged in the prior art (J. Membr. Sci. 2019, 591, 117345; Nat. Mater. 2019, 18, 76-81.) in the research on ion separation membranes to achieve the separation of monovalent cations. 1-3 . Crown ethers can selectively surround and bind specific ions through their ring structures and have high selectivity. The structure of crown ethers can adjust their ion selectivity and affinity by changing the size of the ring and the type of substituents. This diversity allows crown ethers to be designed and synthesized to meet different separation needs. However, the synthesis cost of crown ethers is high, and the hydrolysis and aging of crown ethers often destroy the nanochannels for ion transport, thereby weakening or even reversing the separation selectivity between monovalent cations. The prior art (Angew. Chem. Int. Ed. 2021, 60, 22265-22269.) reports that the introduction of sulfonates can adjust the affinity of ion screening materials and enhance the selectivity for certain specific ions. This helps to achieve efficient separation in complex mixtures, but the permeability of lithium ions during the separation process is not high. At present, most two-dimensional membranes, such as graphene oxide, molybdenum disulfide, metal organic frameworks, and covalent organic framework membranes exhibit better potassium ion permeability, which is not conducive to the extraction of lithium, especially from salt lakes with low lithium content. In summary, it is crucial to construct a separation membrane with a high separation ratio of lithium ions based on two-dimensional materials. Summary of the invention
[0004] The separation of monovalent alkali metal ions has always been a difficult problem in the field of membrane separation. In order to solve the problem of difficulty in separating monovalent cations in the prior art, the inventors first studied Li + , K + 、Na + Factors affecting the transport rate in two-dimensional layered membranes. Studies have found that two-dimensional nanochannels such as vermiculite (V), graphene oxide (GO) and layered double hydroxides (LDH, magnesium aluminum hydrotalcite) all exhibit non-selective but rapid monovalent cation transport. The transport rate of monovalent alkali metal ions in two-dimensional layered membranes is affected by the hydration binding energy of the ions themselves on the one hand, and the interaction between the ions and the interlayer materials on the other hand;
[0005] In order to separate monovalent alkali metal ions, we hope that Li + The difference between the interaction force between the interlayer material and the binding energy of hydrated lithium ions should be as small as possible to accelerate the Li + At the same time, we also hope that other monovalent alkali metal ions M + The difference between the interaction force between the interlayer material and the binding energy of hydrated lithium ions should be as large as possible to slow down the M + transmission.
[0006] Based on this, the present invention seeks a suitable two-dimensional material or a modified two-dimensional material so that the modified two-dimensional material and Li + The difference between the binding energy of the material and the binding energy of hydrated lithium ions is as small as possible, and the difference between the binding energy of the material with other monovalent alkali metal ions and the binding energy of hydrated cations is as large as possible, then a higher separation ratio can be achieved.
[0007] [Monovalent alkali metal ion separation composite membrane]
[0008] The first aspect of the present invention provides a monovalent alkali metal ion separation composite membrane, the composite membrane comprising a two-dimensional material and a heteropoly acid (HPA) distributed between the two-dimensional material layers; the two-dimensional material is selected from vermiculite, graphene oxide or layered double metal hydroxide (LDH);
[0009] The exchange barrier between the heteropolyacid and the monovalent alkali metal ion should satisfy the following relationship:
[0010]
[0011] in, Li + and Li bound to water + The exchange barrier is:
[0012]
[0013] in, For Li + Coordination energy with heteropolyacids; For Li + hydration energy combined with water;
[0014]
[0015] and E HPA are the Gibbs free energies of lithium ion-heteropolyacid complex, bare lithium ion, and heteropolyacid, respectively;
[0016]
[0017] in, and are the Gibbs free energies of hydrated lithium ions, bare lithium ions, and water, respectively;
[0018] M is the M that is coordinated with the heteropoly acid + and water-bound M + The exchange barrier is:
[0019]
[0020] in, M + Coordination energy with heteropolyacids; M + hydration energy combined with water;
[0021]
[0022] and E HPA are the Gibbs free energies of the M ion-heteropolyacid complex, the bare M ion, and the heteropolyacid, respectively;
[0023]
[0024] in, and are the Gibbs free energies of hydrated M ions, bare M ions, and water, respectively;
[0025] M + Selected from K + Or Na + .
[0026] Preferably, M + K + .
[0027] As used herein, "heteropolyacid" refers to a highly symmetrical polyanion formed by connecting a plurality of different types of oxide ions (such as phosphorus, silicon, vanadium, molybdenum, tungsten, etc.) through oxygen bridge bonds. The general formula of these compounds is X m M n O p q- , where X is usually a heteroatom such as phosphorus, silicon, arsenic, etc., and M is a transition metal element such as molybdenum or tungsten. Its structure is usually a complex network formed by a central heteroatom (such as phosphorus, silicon) surrounded by several metal oxygen clusters (such as molybdenum oxygen clusters or tungsten oxygen clusters).
[0028] From the above, we can know that:
[0029]
[0030] The greater the absolute value of the above difference, the greater the + / M + Preferably, the absolute value of the difference is greater than 1 eV, more preferably, the absolute value of the difference is greater than 1.5 eV, and most preferably, the absolute value of the difference is greater than 1.6 eV.
[0031] As a preferred embodiment of the first aspect of the present invention, a monovalent alkali metal ion separation composite membrane is provided, the composite membrane comprising a heteropoly acid and a two-dimensional material; the heteropoly acid is selected from phosphotungstic acid, Keggin-type silicotungstic acid or phosphomolybdic acid; the two-dimensional material is selected from vermiculite, graphene oxide or layered double metal hydroxide (LDH); the monovalent alkali metal ion separation composite membrane is used for monovalent alkali metal ion Li + With K + Or Na + separation.
[0032] As a preferred embodiment of any one of the first aspects of the present invention, the mass percentage of the heteropolyacid in the total mass of the casting solution is not higher than 10%, preferably not higher than 5%, and most preferably 0.5-5%.
[0033] As a preferred embodiment of any embodiment of the first aspect of the present invention, the two-dimensional material is vermiculite, and the heteropoly acid is Keggin-type phosphotungstic acid (PTA). Experiments show that the highest Li + / M + separation ratio.
[0034] As a preferred embodiment of any embodiment of the first aspect of the present invention, the heteropoly acid and the two-dimensional material are connected by non-covalent bonds or by covalent bonds. In the example of non-covalent bond connection, there is at least hydrogen bond interaction between the heteropoly acid and the two-dimensional material.
[0035] As a preferred embodiment of any one of the first aspects of the present invention, the thickness of the composite film is 0.5-5 μm. Preferably, the thickness of the composite film is 0.5-2 μm.
[0036] As a preferred embodiment of any one of the first aspects of the present invention, the lithium ion permeability and potassium ion permeability of the composite membrane are (2-18): 1. The higher the lithium ion permeability, the higher the lithium ion transmission rate of the composite membrane.
[0037] As a preferred embodiment of any one of the first aspects of the present invention, the lithium ion permeability of the composite membrane is 0.3-1.3 mol m -2 h -1 .
[0038] As a preferred embodiment of any embodiment of the first aspect of the present invention, under the condition of an applied electric field of 0.8 V / cm, the electrodialysis lithium ion flux of the composite membrane is not less than 2.96 mol m -2 h -1 .
[0039] As a preferred embodiment of any embodiment of the first aspect of the present invention, under the condition of an applied electric field of 0.8 V / cm, the lithium / potassium ion two-component separation ratio of the composite membrane is not less than 3, preferably not less than 5, and most preferably not less than 6.
[0040] [Method for preparing monovalent alkali metal ion separation composite membrane]
[0041] The second aspect of the present invention provides a method for preparing a monovalent alkali metal ion separation composite membrane according to any one of the schemes of the first aspect of the present invention, comprising:
[0042] A two-dimensional material dispersion solution containing a heteropoly acid is provided as a casting solution; the heteropoly acid is selected from phosphotungstic acid, Keggin-type silicotungstic acid or phosphomolybdic acid, and the two-dimensional material is selected from vermiculite, graphene oxide or layered double metal hydroxide; in the casting solution, the mass concentration of the two-dimensional material is 0.02-0.2 mg / mL, and the mass percentage of the heteropoly acid is 0.5-10%;
[0043] The casting solution is made into a monovalent alkali metal ion separation composite membrane.
[0044] As a preferred embodiment of any one of the second aspects of the present invention, before preparing the monovalent alkali metal ion separation composite membrane, the casting solution is placed stably at 2 to 8° C. for 4 to 12 hours.
[0045] As a preferred embodiment of any embodiment of the second aspect of the present invention, the heteropolyacid is Keggin-type phosphotungstic acid.
[0046] As a preferred embodiment of any embodiment of the second aspect of the present invention, the two-dimensional material is vermiculite.
[0047] [Application of monovalent alkali metal ion separation composite membrane]
[0048] The third aspect of the present invention provides the use of a monovalent alkali metal ion separation composite membrane of any one of the schemes of the first aspect of the present invention in the separation of monovalent alkali metal ions, wherein the monovalent alkali metal ions include Li + , also comprising selected from K + Or Na + Preferably, the monovalent alkali metal ion comprises or is Li + and K + .
[0049] As a preferred embodiment of any embodiment of the third aspect of the present invention, the application is performed in an external electric field. Preferably, the external electric field is 0.27V / cm to 0.8V / cm, and most preferably 0.8V / cm.
[0050] Beneficial Effects
[0051] Compared with the prior art, the present invention has the following beneficial effects:
[0052] (1) The present invention combines a heteropoly acid with a two-dimensional material to prepare a monovalent alkali metal ion separation composite membrane, and selects a heteropoly acid with appropriate coordination energy with different monovalent alkali metal ions by the size of the exchange barrier, so that the heteropoly acid and Li + The difference between the coordination energy of the lithium ions and the binding energy of the hydrated lithium ions is smaller, thereby realizing the rapid exchange of lithium ions between the layers and forming a rapid transmission channel for lithium ions between the membranes, making Li + The transport rate in the membrane is higher than that of other monovalent alkali metal ions, achieving the purpose of separating lithium ions with a high separation ratio.
[0053] (2) In the present invention, the heteropoly acid is selected from phosphotungstic acid, Keggin-type silicotungstic acid or phosphomolybdic acid, and the two-dimensional material is selected from vermiculite, graphene oxide and layered double metal hydroxide. In this system, the transmission rate of lithium ions is higher than that of potassium ions. It is preferred to use a monovalent alkali metal ion separation composite membrane prepared by combining Keggin-type phosphotungstic acid (PTA) with a two-dimensional material. Among the many heteropoly acids, Keggin-type phosphotungstic acid and Li + The difference between the coordination energy of the lithium ions and the binding energy of the hydrated lithium ions is smaller, so the lithium ions are quickly exchanged between the layers, forming a fast transmission channel for lithium ions between the membranes, making Li + The transfer rate in the membrane is higher than that of other monovalent alkali metal ions (potassium ions or sodium ions), so the purpose of separating lithium ions with a high separation ratio is achieved.
[0054] (3) In the monovalent alkali metal ion separation composite membrane of the present invention, the Keggin-type phosphotungstic acid achieves the ideal separation of monovalent alkali metal ions within a specific addition mass percentage range; in some embodiments, the lithium / potassium ion two-component separation ratio reaches 6, indicating that the composite membrane has excellent monovalent alkali metal ion separation performance.
[0055] (4) The preparation process of the present invention is simple and has low requirements for preparation conditions, which is conducive to the large-scale production and application of monovalent alkali metal ion separation composite membranes; in addition, the monovalent alkali metal ion separation composite membranes with a high separation ratio of the present invention are expected to be applied to various lithium resource mining and extraction fields (including lithium extraction from salt lakes, lithium extraction using mineral processing wastewater, etc.), thereby improving the utilization efficiency of lithium resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 It is a schematic diagram of the structure of the monovalent alkali metal ion separation composite membrane of the present invention.
[0057] Figure 2 SEM cross-sectional images of PTA@V-3, D-PTA@V-5, PTA@GO-3 and PTA@LDH-3 composite films.
[0058] Figure 3 Figure 2 shows the positive permeability test data of HPA@2D-x composite membrane: (a) The effect of PTA doping amount on Li + Permeability, Li + / K + The effect of ideal separation ratio (permeability ratio); (b) the effect of heteropoly acid type on Li + Permeability, Li + / K + Effect of ideal separation ratio (permeability ratio): PTA@V-3, PMA@V-3, STA@V-1, and D-PTA@V-5 prepared in Example 2; (c) Effect of PTA doping on Li + / K + Influence of ideal separation ratio (ratio of permeabilities).
[0059] Figure 4 This is the electrodialysis test data of PTA@V-3 composite membrane under different external electric fields. Inset: separation ratio of pure vermiculite membrane and PTA@V-3 composite membrane.
[0060] Figure 5 This is the 24-hour positive permeability test data of the PTA@V-3 composite membrane.
[0061] Figure 6Lithium ion recognition in heteropolyacid-functionalized two-dimensional membranes. (a) Ion exchange equilibrium of three states during transport in heteropolyacid-functionalized two-dimensional membranes: hydrated ions (M + @H2O), ions of heteropoly acid ligands (M + @HPA) and ions acting on the two-dimensional membrane channel wall (M + @2D); (b) With M + @H2O and M + With the increase of exchange barrier (ΔE) between HPA, the ion permeability increases exponentially; (c) Li + / K + The difference between the ideal selectivity and the calculated exchange energy barrier (where and (d) Li of three PTA functionalized 2D membranes + / K + Ideal selectivity and calculated exchange barriers for lithium ion transport in three 2D material membranes (where is a negative value, and are all positive values). DETAILED DESCRIPTION
[0062] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.
[0063] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0064] Reagent Manufacturer:
[0065] Vermiculite was purchased from Shijiazhuang Chenxing Industrial Co., Ltd., thermally expanded vermiculite.
[0066] Graphene oxide was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. and freeze-dried graphene oxide.
[0067] Phosphotungstic acid was purchased from Tianjin Xiensi Biochemical Technology Co., Ltd.
[0068] Keggin type silicotungstic acid was purchased from Tianjin Xiensi Biochemical Technology Co., Ltd.
[0069] Phosphomolybdic acid was purchased from Tianjin Xiensi Biochemical Technology Co., Ltd.
[0070] The metal ions were analytical grade metal chlorides.
[0071] Synthesis of Layered Double Hydroxide (Mg-Al LDH) Nanosheets:
[0072] Dissolve 20mmol Mg(NO3)2·6H2O, 10mmol Al(NO3)3·9H2O and 26mmol hexamethylenetetramine in 80mL water, place the mixture in a high pressure reactor and heat at 140°C, centrifuge the precipitate in water and ethanol (10000rpm, 10-15min) for 3 times each, and dry at room temperature. Add a mixed solution of hydrochloric acid containing 300mL NaNO3 and 5mM HNO3, shake in a shaker under a nitrogen atmosphere for 1 day, disperse in water and ethanol and centrifuge (10000rpm, 10-15min) for 3 times each. Add 100mL formamide, shake in a shaker under a nitrogen atmosphere for 2 days, filter to remove the unpeeled particles, and obtain a formamide dispersion of Mg-Al LDH nanosheets.
[0073] Preparation of Well-Dawson type phosphotungstic acid: Dissolve 10g Na2WO4·2H2O and 35mL water, heat to boiling, slowly drop 15mL 85% H3PO4, add 1mL H2O2 under stirring. Reflux the resulting solution for 3h, add 10g KCl solid after cooling, stir for 1h, and filter. Add a small amount of water, recrystallize, filter, cool in ice water, and filter. Collect the crystals and dry.
[0074] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. The degree of flexibility for a particular variable can be easily determined by one skilled in the art.
[0075] Concentration, amount and other numerical data can be presented in range format herein.It should be understood that such range format is only used for convenience and simplicity, and should be flexibly interpreted as not only including the numerical value clearly described as range limit, but also including all single numerical values or sub-ranges contained in the range, just as each numerical value and sub-range are clearly described.For example, the numerical range of about 1 to about 4.5 should be interpreted as not only including the limit value of 1 to about 4.5 clearly described, but also including single numerals (such as 2,3,4) and sub-ranges (such as 1 to 3,2 to 4, etc.).The same principle is applicable to the scope of only narrating a numerical value, such as "less than about 4.5", which should be interpreted as including all the above-mentioned values and ranges.In addition, no matter how the breadth of the described range or feature is, this explanation should be applicable.
[0076] Example 1 Calculation of exchange barrier
[0077] In the present invention, a heteropoly acid capable of coordinating with a monovalent metal ion is selected as a ligand. In order to gain a deeper understanding of the lithium ion selectivity of the heteropoly acid functionalized two-dimensional membrane from a molecular perspective, the present invention studies and establishes a diffusion model based on the interaction between cations and recognition sites and water. Regarding the cation transport of the pearlite-like membrane with interlayer water, the coordination of cations with heteropoly acid ligands and the exchange between interlayer water, as well as the interaction between cations and the capillary wall of the two-dimensional channel should be considered.
[0078] The compensation between the coordination and hydration of the cations is considered as the following exchange equilibrium (Eq. (9)), and as shown in Eq. (10), the experimentally obtained ion permeability (k) increases exponentially with the corresponding exchange barrier (ΔE) (Eq. (11)):
[0079]
[0080] k∝exp(ΔE)(10)
[0081]
[0082] The competition between the coordination process and the hydration process becomes an obstacle to the migration of cations, so the lower the exchange barrier (|ΔE|), the easier the cation transport in the heteropolyacid functionalized two-dimensional membrane.
[0083] There are two types of heteropolyacids: Keggin type and Wells-Dawson type. For example, Keggin type phosphotungstic acid (H3PW 12 O 40 , PTA), phosphomolybdic acid (Keggin type, H3PMo 12 O 40 , PMA), silicotungstic acid (Keggin type, H4SiW 12 O 40 , STA) and Wells-Dawson type phosphotungstic acid (α-K6P2W 18 O 62 , D-PTA). Keggin type heteropolyacid anion X + nM 12 O 40 - (where M usually refers to tungsten or molybdenum, and X can be almost any other cation, such as phosphorus, silicon, etc.) is composed of a central heteroatom (X) and four groups of three MO octahedra. The formula of the Wells-Dawson type heteropolyacid anion is X + nM 18 O 62 -, which can be regarded as a combination of two Keggin units. The cavity can be connected with a monovalent cation (usually with a diameter of between).
[0084] The functionalized two-dimensional nanochannels are constructed of nanosheets, such as vermiculite (V), graphene oxide (GO) and layered double hydroxides (LDH), all of which exhibit non-selective but rapid monovalent cation transport. The interaction between the cations and the capillary walls of the two-dimensional channels is much smaller than the coordination effect between the cations and the heteropolyacid ligands. Therefore, the specific numerical influence of the interaction between the cations and the capillary walls of the two-dimensional channels can be ignored in the selection of heteropolyacids for the composite membrane of the present invention.
[0085] By functionalizing 2D nanochannels with different types of heteropolyacids, the interactions of monovalent cations with heteropolyacids and interlayer water were studied to identify a system that can be effectively used for the separation of monovalent alkali metal ions.
[0086] Therefore, in order to achieve a high separation ratio of monovalent alkali metal ions, the selection of heteropolyacids should satisfy formula (1):
[0087]
[0088] in, The exchange barrier between Li+ coordinated with heteropolyacid and Li+ bound with water:
[0089]
[0090] in, For Li + Coordination energy with heteropolyacids; For Li + hydration energy combined with water;
[0091]
[0092] and E HPA are the Gibbs free energies of lithium ion-heteropolyacid complex, bare lithium ion, and heteropolyacid, respectively;
[0093]
[0094] in, and are the Gibbs free energies of hydrated lithium ions, bare lithium ions, and water, respectively;
[0095] M is the M that is coordinated with the heteropoly acid + and water-bound M + The exchange barrier is:
[0096]
[0097] in, M+ Coordination energy with heteropolyacids; M + hydration energy combined with water;
[0098]
[0099] and E HPA are the Gibbs free energies of the M ion-heteropolyacid complex, the bare M ion, and the heteropolyacid, respectively;
[0100]
[0101] in, and are the Gibbs free energies of hydrated M ions, bare M ions, and water, respectively;
[0102] M + Selected from K + Or Na + .
[0103] Specifically, the calculation method is as follows: All first-principles calculations were performed using the Vienna Ab initio Simulation Package. The ion-electron interaction was described using the projector augmented wave method. The generalized gradient approximation combined with the Perdew-Burke-Ernzerhof (PBE) method was used to treat the interaction of electron exchange-correlation energy. The Gamma center k-point grid was used in this work, and the cutoff energy was set to 520 eV. The energy convergence criterion and the force convergence criterion were set to 1×10-5 eV and 1×10-5 eV, respectively. The Packing function in Material Studio is used to build a model to study the hydration energy of metals in water. The calculation conditions are the same as those mentioned above. + Take the PTA system as an example:
[0104]
[0105]
[0106]
[0107]
[0108] E PTA =-463.0112eV According to the formula:
[0109]
[0110]
[0111]
[0112]
[0113] According to the formula:
[0114]
[0115]
[0116] Calculate in the same way
[0117]
[0118] The results show that the PTA strategy This indicates that the transfer rate of lithium ions between two-dimensional material layers is greater than that of potassium ions and sodium ions.
[0119] On this basis, the present invention studies and calculates the Li + , K + Transfer rate:
[0120] In the PMA system, This indicates that the transfer rate of lithium ions between two-dimensional material layers is greater than that of potassium ions.
[0121] In the STA system, This indicates that the transfer rate of lithium ions between two-dimensional material layers is greater than that of potassium ions.
[0122] In the D-PTA system, This indicates that the transfer rate of lithium ions between two-dimensional material layers is greater than that of potassium ions.
[0123] The following will experimentally verify the composite membrane for efficient separation of monovalent alkali metal ions implemented according to the above scheme.
[0124] Example 2 HPA@V composite membrane
[0125] 1. Membrane preparation
[0126] This embodiment provides a method for preparing a monovalent alkali metal ion separation composite membrane with a high separation ratio by doping an inorganic material (using a heteropoly acid as an inorganic material and vermiculite (V) as a two-dimensional material), and the specific steps are as follows:
[0127] Step 1: Preparation of casting solution;
[0128] The single-layer vermiculite nanosheets are peeled off by ion intercalation, which specifically includes the following steps:
[0129] Weigh a certain amount of heat-expanded vermiculite powder and dissolve it in a saturated sodium chloride solution, heat it at 100 ° C and stir it at 1000 rpm for 48 hours. Wash it with deionized water, and heat and stir the obtained sodium-exchanged vermiculite filter cake in a 2M lithium chloride solution for 24 hours. Wash it with deionized water, and disperse the obtained lithium-exchanged vermiculite filter cake in deionized water and ultrasonicate for 30 minutes. Finally, centrifuge 10 times at a speed of 5000 rpm for many times, and a single centrifugation time of 20 minutes to obtain a colloid, and add appropriate amount of water to obtain a monolayer vermiculite nanosheet dispersion. In the present embodiment, the lithium-exchanged vermiculite filter cake is dispersed in deionized water for 30 minutes of ultrasonication, and the precipitation is removed by centrifugation at a speed of 3000 rpm for 10 minutes, and the supernatant is removed by centrifugation at a speed of 10000 rpm for 10 minutes, and a total of 8 centrifugations are performed to obtain a colloid.
[0130] The single-layer vermiculite nanosheet dispersion (0.02 mg / ml) prepared in step 1 is doped with a heteropoly acid at a certain mass percentage to obtain a casting solution with a total mass of 20 g, wherein the mass percentage of the heteropoly acid in the total mass of the casting solution is 0.5-10wt% solution. The above solutions are mixed evenly and stably maintained at 4°C for 8 hours to obtain a HPA@Vx casting solution, wherein HPA represents heteropoly acid, V represents single-layer vermiculite nanosheets, and x represents the mass percentage of the heteropoly acid in the total mass of the casting solution.
[0131] Step 2: Preparation of high separation ratio monovalent cation separation membrane;
[0132] The porous nylon-66 membrane is placed on a suction filtration device, and the HPA@Vx casting solution obtained in step 1 is added and filtered to obtain the HPA@Vx monovalent alkali metal ion separation composite membrane. The thickness of the monovalent alkali metal ion separation composite membrane can be 0.5-5 μm. In this embodiment, the thickness of the monovalent alkali metal ion separation composite membrane is about 0.5 μm.
[0133] In one embodiment, other conditions are the same as above, except that a single layer of vermiculite nanosheets with a concentration of 0.02 mg / ml is used for filtration to form a membrane, and the obtained membrane is recorded as V membrane.
[0134] In one embodiment, other conditions are the same as those described above, except that a single-layer vermiculite nanosheet with a concentration of 0.02 mg / ml is used, the heteropoly acid is PTA, the mass percentage of PTA added to the total mass of the casting liquid is 0.5%, and the obtained monovalent alkali metal ion separation composite membrane is recorded as PTA@V-0.5 membrane.
[0135] In one embodiment, other conditions are the same as those described above, except that a single-layer vermiculite nanosheet with a concentration of 0.02 mg / ml is used, the heteropoly acid is PTA, the mass percentage of PTA added to the total mass of the casting liquid is 1%, and the obtained monovalent alkali metal ion separation composite membrane is recorded as PTA@V-1 membrane.
[0136] In one embodiment, other conditions are the same as above, except that a single layer of vermiculite nanosheets with a concentration of 0.02 mg / ml is used, the heteropoly acid is PTA, and the mass percentage of PTA addition to the total mass of the casting solution is 3%. The obtained monovalent alkali metal ion separation composite membrane is recorded as PTA@V-3 membrane. Figure 1 As shown, it is a schematic diagram of the structure of the inorganic material doped high separation ratio monovalent alkali metal ion separation composite membrane of the present invention; Figure 2 As shown in a, the PTA@V-3 film exhibits a typical layered stacking structure and is well stacked.
[0137] In one embodiment, other conditions are the same as those described above, except that a single-layer vermiculite nanosheet with a concentration of 0.02 mg / ml is used, the heteropoly acid is PTA, the mass percentage of PTA added to the total mass of the casting liquid is 5%, and the obtained monovalent alkali metal ion separation composite membrane is recorded as PTA@V-5 membrane.
[0138] In one embodiment, other conditions are the same as those described above, except that a single-layer vermiculite nanosheet with a concentration of 0.02 mg / ml is used, the heteropoly acid is PTA, the mass percentage of PTA added to the total mass of the casting liquid is 10%, and the obtained monovalent alkali metal ion separation composite membrane is recorded as PTA@V-10 membrane.
[0139] In one embodiment, other conditions are the same as those described above, except that a single-layer vermiculite nanosheet with a concentration of 0.02 mg / ml is used, the heteropoly acid is PMA, the mass percentage of PMA in the total mass of the casting liquid is 3%, and the obtained monovalent alkali metal ion separation composite membrane is recorded as PMA@V-3 membrane.
[0140] In one embodiment, other conditions are the same as those described above, except that a single-layer vermiculite nanosheet with a concentration of 0.02 mg / ml is used, a heteropoly acid is used as STA, the mass percentage of STA in the total mass of the casting solution is 1%, and the obtained monovalent alkali metal ion separation composite membrane is recorded as STA@V-1 membrane.
[0141] In one embodiment, other conditions are the same as above, except that a single layer of vermiculite nanosheets with a concentration of 0.02 mg / ml is used, the heteropoly acid is D-PTA, the mass percentage of D-PTA in the total mass of the casting solution is 5%, and the obtained monovalent alkali metal ion separation composite membrane is recorded as D-PTA@V-5 membrane. Figure 2 As shown in b, SEM shows that the D-PTA@V-5 composite membrane also presents a typical layered stacking structure; Figure 3 As shown in b, in the forward permeability test, the D-PTA@V-5 composite membrane has a better lithium ion permeability than potassium ions.
[0142] 2. Membrane Characterization
[0143] The composite films with different doping ratios obtained in step 2 are dried, and the stacking conditions in the composite films with different ratios are known based on the SEM cross-sectional images of some composite films.
[0144] 3. Membrane performance test
[0145] The composite membranes with different doping ratios were subjected to single ion system forward osmosis test and binary ion system electrodialysis test.
[0146] (1) Positive osmosis test:
[0147] The positive permeability test was performed using an H-type sample cell. The composite membrane was sealed in the middle of the sample cell with a clamp. A 0.1M chloride salt solution (lithium chloride, sodium chloride or potassium chloride) was placed on the feed side, with the membrane facing the feed side. An equal volume of deionized water was added to the permeate side and stirred. The conductivity of the permeate solution was recorded once a minute by a conductivity meter (SevenDirect SD30). The formula for calculating the ion permeability of a single ion system is:
[0148]
[0149] C t Represents the ion concentration of the osmotic solution at the time of sampling (mol L -1 ), C0 represents the initial ion concentration of osmotic pressure measurement (mol L -1 ), V represents the volume of deionized water on the permeate side (L), and A represents the effective membrane area (m -2 ), t represents the test time interval (h). Three different samples of each type of membrane were tested to obtain the average value of the permeability and evaluate the standard deviation.
[0150] Selectivity in single-ion systems The calculation formula is:
[0151]
[0152] M + Represents Na+ and K + ;
[0153] (2) Electrodialysis test:
[0154] Taking the PTA@V-3 membrane obtained in step 2 as an example, the PTA@V-3 membrane obtained in step 2 and two commercial anion exchange membranes (FAA-50, Fumatech GmbH) were used to separate the four chambers of electrodialysis. The PTA@V-3 membrane was placed in the middle, facing the anode chamber. Binary ion system electrodialysis tests were carried out under external electric fields of 0.2-0.8V / cm. The cathode chamber and the anode chamber were respectively filled with 200mL of 0.3M sodium sulfate solution. The dilution chamber was filled with 200mL of 0.05M lithium sulfate / potassium sulfate solution, and the concentration chamber was filled with 200mL of 0.0025M sulfuric acid solution. The mass concentrations of lithium ions and potassium ions in the concentration chamber were analyzed by ion chromatography (ECOIC, Metrohm). Before the test, a series of electrolyte solutions with different concentrations were prepared, and a calibration curve was obtained by ion chromatography. The calculation formula for the ion permeability of the binary ion system is as follows:
[0155]
[0156]
[0157] Represents mass permeability (gm -2 h -1 ). i represents the molar permeability (mol m -2 h -1 ),ρ t The ion mass concentration in the concentration chamber at the time of sampling (ppm), ρ0 represents the initial ion mass concentration (ppm), M i Indicates atomic molar mass (g mol -1 ), A represents the effective membrane area (m -2 ), t represents the test time interval (h).
[0158] The separation factor of the binary ion system is calculated as follows:
[0159]
[0160]
[0161] Three different membrane samples were also tested to obtain the average value of the permeability and to estimate the standard deviation.
[0162] like Figure 3As shown in a and 3b, it can be seen that the preferred doping inorganic material of the HPA@Vx composite membrane prepared in this embodiment is PTA, and the preferred doping mass percentage of the PTA@Vx composite membrane is 3%. Among them, the single-component forward osmosis test ion permeability of each membrane under the same conditions is:
[0163] Table 1 Ion permeability of composite membranes in single-component forward osmosis experiments
[0164]
[0165]
[0166] The results show that in the single-component positive osmosis experiment, when the mass percentage of PTA in the casting liquid is between 0 and 10%, the lithium ion permeability is higher than the potassium ion permeability, but when the mass percentage of PTA in the casting liquid is 0, 0.5% and 10%, the ratio of the single-component lithium ion to potassium ion ion permeability is lower than 3, and when the mass percentage of PTA in the casting liquid is 1%, 3% and 5%, the ratio of the single-component lithium ion to potassium ion ion permeability is higher than 3, reaching the highest value when the mass percentage of PTA in the casting liquid is 3%. When the mass percentage of PTA in the casting liquid is 0 and 3%, the lithium ion permeability is higher than the sodium ion permeability, but when the mass percentage of PTA in the casting liquid is 0, the difference between the lithium ion permeability and the sodium ion permeability is very small, and when the mass percentage of PTA in the casting liquid is 3%, the ratio of the lithium ion permeability to the sodium ion permeability reaches more than 8.
[0167] The ion separation ratio of the two-component electrodialysis experiment under the same conditions of PTA@V-3 and V membrane is:
[0168] Table 2 Two-component electrodialysis ion separation ratio of composite membrane (0.8 V / cm applied electric field)
[0169] membrane Separation factor of lithium / potassium ions V 1.43 PTA@V-3 6.07
[0170] like Figure 4 As shown in Figure 2, with the increase of the applied electric field, the separation factor of the PTA@V-3 composite membrane in the binary ion system gradually increases; under the condition of an applied electric field of 0.8 V / cm, the separation factor of lithium / potassium ions is as high as 6.07 (Table 2). Under this condition, the electrodialysis lithium ion flux of the PTA@V-3 composite membrane is 2.96 mol m -2 h -1 .
[0171] 4. Stability test of PTA@V-3 composite membrane
[0172] The stability of the composite membrane was evaluated by subjecting it to a single ion system forward permeation test as described in step 4 for up to 24 hours.
[0173] like Figure 5 As shown, the lithium ion permeability and lithium / potassium ion separation ratio of the PTA@V-3 composite membrane remained stable during the 24 h test.
[0174] Example 3 HPA@GO composite membrane
[0175] This embodiment provides a method for preparing a monovalent cation separation composite membrane with a high separation ratio by doping inorganic materials (PTA as the inorganic material and graphene oxide as the two-dimensional material).
[0176] The freeze-dried graphene oxide nanosheets were dispersed in deionized water (0.02 mg / ml) and stirred overnight. The dispersion was centrifuged to remove the precipitate to obtain a colloid, and a suitable amount of water was added to obtain a single-layer graphene oxide nanosheet dispersion, which was doped with phosphotungstic acid according to a certain mass percentage (3wt%) and filtered to obtain the PTA@GO-3 composite membrane. The above characterization and performance tests were performed.
[0177] like Figure 2 As shown in c, SEM shows that the PTA@GO-3 composite film is well stacked.
[0178] like Figure 3 As shown in Figure c, the separation performance of the PTA@GO-3 composite membrane prepared in this example in a single-component ion forward osmosis system can be obtained. Among them, the GO membrane without PTA can hardly separate Li + and K + , while the PTA@GO-3 composite membrane with 3% PTA doping has a Li + / K + The separation ratio is about 4 (lithium ion permeability: potassium ion permeability is 4:1). After doping, the separation ratio is significantly improved.
[0179] Example 4 HPA@LDH composite membrane
[0180] This embodiment provides a method for preparing a monovalent alkali metal ion separation composite membrane with a high separation ratio by doping inorganic materials (PTA as the inorganic material and layered double hydroxide as the two-dimensional material).
[0181] The formamide dispersion (0.02 mg / ml) of Mg-Al layered double hydroxide nanosheets was mixed with a certain mass percentage (3 wt%) of doped phosphotungstic acid, and filtered to obtain the PTA@LDH-3 cationic separation membrane. The above characterization and performance tests were performed.
[0182] like Figure 2 As shown in (d), SEM shows that the PTA@LDH-3 composite membrane is tightly stacked.
[0183] like Figure 3 As shown in Figure c, it can be seen that the separation performance of the PTA@LDH-3 composite membrane prepared in this example in a monovalent ion system. Among them, the LDH membrane without PTA doping can hardly separate Li + and K + , while the PTA@LDH-3 composite membrane doped with 3% PTA has a Li + / K + The separation ratio is about 3 (lithium ion permeability: potassium ion permeability is 3:1). After doping, the separation ratio is significantly improved.
[0184] Combining the results obtained under the theoretical guidance of Example 1 with the experiments in Example 2, the analysis results are as follows:
[0185] By Li + and K + Taking the selectivity in PTA as an example, the exchange barrier between lithium ions and PTA is calculated in Example 1. is -1.90eV, and its absolute value is The absolute value is 1.62eV lower ( =-3.52 eV), and in the experiment of Example 2, it was proved that Li + / K + The selectivity (permeability ratio) can reach up to 16.
[0186] According to the method in Example 1, as M + @H2O and M + The increase of exchange barrier (ΔE) between PTA@V-3 film and Mg 2+ , K + 、Na + , Ca 2+ , Li + The ion permeability increases exponentially.
[0187] In the D-PTA@V system, it is calculated in Example 1 that The absolute value of The absolute value of is 0.34 eV lower than that of Li + / K + The selectivity (ratio of permeability) is only 2.23 ( Figure 6 c) Therefore, the selectivity between monovalent cations in functionalized vermiculite membranes mainly depends on the exchange barrier between the coordination process and the hydration process. + The exchange barrier is less than K + When exchanging the potential barrier, Li + The transmission rate is greater than K + .Li + and K+ The greater the difference in exchange barriers, i.e. The larger the absolute value of the difference, the + / K + The higher the selectivity.
[0188] When the same percentage of heteropolyacid was used to prepare the composite membrane (PTA 3%), the calculation results showed that Li + The exchange barrier for transport into the vermiculite channel is negative, the lowest among the three materials, so lithium ions can more easily enter the two-dimensional material channel formed by vermiculite ( Figure 6 d), and also demonstrated that vermiculite as a 2D material plays a synergistic role in lithium ion recognition of heteropolyacid functionalized membranes.
[0189] Therefore, to construct a lithium ion recognition membrane, it is necessary to reduce the exchange barrier between the lithium ion hydration state and its coordination state with the heteropoly acid and the state of interaction with the two-dimensional nanosheet. In summary, the experimental verification results show that among the four heteropoly acids, the most preferred heteropoly acid ligand in the construction of the monovalent alkali metal ion separation membrane system constructed by vermiculite / GO / LDH two-dimensional material is PTA, which is consistent with the guidance in Example 1.
[0190] In addition to the above embodiments, other heteropolyacid materials can be replaced for doping, such as Keggin-type silicotungstic acid, phosphomolybdic acid and other heteropolyacids, as long as they meet the requirements of Li + and M + Heteropoly acids based on the principle of difference in exchange barriers can be used to construct composite membranes for separation of monovalent alkali metal ions.
[0191] The above content is a schematic description of the present invention and its implementation methods, which is not restrictive. What is shown in the embodiment is only one of the implementation methods of the present invention, and the actual implementation method is not limited thereto. Therefore, if a person of ordinary skill in the art is inspired by it and designs implementation methods and embodiments similar to the technical solution without creative design without departing from the purpose of the invention, they should all fall within the scope of protection of the present invention.
Claims
1. A monovalent alkali metal ion separation composite membrane, characterized in that: The composite film comprises a two-dimensional material and a heteropoly acid distributed between the two-dimensional material layers; the two-dimensional material is selected from vermiculite, graphene oxide or layered double metal hydroxide; The exchange barrier between the heteropolyacid and the monovalent alkali metal ion should satisfy the following relationship: in, Li + and Li bound to water + The exchange barrier is: in, For Li + Coordination energy with heteropolyacids; For Li + hydration energy combined with water; and E HPA are the Gibbs free energies of lithium ion-heteropolyacid complex, bare lithium ion, and heteropolyacid, respectively; in, and are the Gibbs free energies of hydrated lithium ions, bare lithium ions, and water, respectively; M is the M that is coordinated with the heteropoly acid + and water-bound M + The exchange barrier is: in, M + The coordination energy of the ion binding to the heteropolyacid; M + The hydration energy of ions combined with water; and E HPA are the Gibbs free energies of the M ion-heteropolyacid complex, the bare M ion, and the heteropolyacid, respectively; in, and are the Gibbs free energies of hydrated M ions, bare M ions, and water, respectively; M + Selected from K + Or Na + .
2. A monovalent alkali metal ion separation composite membrane, characterized in that: The composite film comprises a two-dimensional material and a heteropoly acid distributed between the two-dimensional material layers; the heteropoly acid is selected from phosphotungstic acid, Keggin-type silicotungstic acid or phosphomolybdic acid, and the two-dimensional material is selected from vermiculite, graphene oxide or layered double metal hydroxide.
3. The monovalent alkali metal ion separation composite membrane according to claim 1 or 2, characterized in that: The two-dimensional material is selected from vermiculite, and the heteropoly acid is Keggin-type phosphotungstic acid.
4. The monovalent alkali metal ion separation composite membrane according to any one of claims 1 to 3, characterized in that: The mass percentage of the heteropoly acid in the monovalent alkali metal ion separation composite membrane is not higher than 10%.
5. The monovalent alkali metal ion separation composite membrane according to claim 4, characterized in that: The thickness of the composite film is 0.5-5 μm.
6. The monovalent alkali metal ion separation composite membrane according to claim 5, characterized in that: The lithium ion permeability of the composite membrane is (2-18):1; the lithium ion permeability of the composite membrane is 0.3-1.3 mol m -2 h -1 .
7. The monovalent alkali metal ion separation composite membrane according to claim 5, characterized in that: Under the condition of an applied electric field of 0.8 V / cm, the lithium / potassium ion two-component separation ratio of the composite membrane is not less than 6.
8. The method for preparing a monovalent alkali metal ion separation composite membrane according to any one of claims 1 to 7, characterized in that: The following steps are involved: A two-dimensional material dispersion solution containing a heteropoly acid is provided as a casting solution; the heteropoly acid is selected from phosphotungstic acid, Keggin-type silicotungstic acid or phosphomolybdic acid, and the two-dimensional material is selected from vermiculite, graphene oxide or layered double metal hydroxide; in the casting solution, the mass concentration of the two-dimensional material is 0.02-0.2 mg / mL, and the mass percentage of the heteropoly acid is 0.5-10%; The casting solution is made into a monovalent alkali metal ion separation composite membrane.
9. The method for preparing a monovalent alkali metal ion separation composite membrane according to claim 8, characterized in that: Before preparing the monovalent alkali metal ion separation composite membrane, the casting solution is placed at 2 to 8° C. for 4 to 12 hours.
10. Use of the monovalent alkali metal ion separation composite membrane according to any one of claims 1 to 7 in the separation of monovalent alkali metal ions, wherein the monovalent alkali metal ions comprise Li + , also comprising selected from K + Or Na + One or both of the following.
Citation Information
Patent Citations
Multi-acid multi-base graft copolymer dispersants
CN105517697A
Heteropolyacid / graphene oxide composite and preparation method and application thereof
CN106824275A
Preparation method and application of heteropolyacid molecular cluster intercalated reduced graphene oxide separation membrane
CN117379989A
Ion conductive composite membrane using inorganic conductor and method of manufacturing the same
US20070015022A1
